KEBERLANJUTAN PERKEBUNAN KELAPA SAWIT DI INDONESIA DAN PROSPEK PENGEMBANGAN DI KAWASAN PERBATASAN - Ngadi Ngadi; Mita Noveria (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2017)
Palm oil plantation has a significant role in creation of job opportunity and welfare of society. However, there are still many problems challenged in maintaining sustainability of palm oil plantation. This paper aims to assess sustainability of palm oil plantation from social and economy aspects and also the prospect of development of palm oil plantation in border areas. This paper analyses the data of some research conducted by researchers of the Research Centre for Population and the Deputy of Social Sciences and Humanities, Indonesian Institute of Sciences in the province of South Sumatra and Indonesia-Malaysia border areas in West, East, and North Kalimantan. The research shows that in 2014 palm oil plantation has created 5.2 millions job opportunity in Indonesia. In border areas, particularly, development of palm oil plantation has generated job opportunities for Indonesian workers who previously worked in Malaysia and those who intend to work in the neighbouring country. Nevertheless, many palm oil plantation have not been sustainably managed in term of institution and access to land. Weak institutionality in oil palm plantations caused some institutional farmers (KUD) to be unable to operate. On the other hand, low access to land created many cases of land conflicts in palm oil plantations. The situation has brought about the low income of labor in palm oil plantations. Sustainable palm oil plantations in Indonesia can only be created through improvements to farmer institutions, access to land and land productivity. Keywords: Sustainable palm oil, plantation labor, South Sumatra, Border areas ABSTRAKPerkebunan kelapa sawit telah memberikan peran positif terhadap penciptaan kesempatan kerja dan kesejahteraan masyarakat. Meskipun demikian, komoditas ini masih menghadapi permasalahan keberlanjutan usaha. Paper ini bertujuan mengkaji keberlanjutan perkebunan kelapa sawit dari aspek sosial ekonomi dan prospek pengembangannya di wilayah perbatasan. Data yang analisis adalah hasil penelitian peneliti-peneliti Pusat Penelitian Kependudukan Lembaga Ilmu Pengetahuan Indonesia (LIPI) dan Kedeputian Bidang Ilmu Pengetahuan Sosial dan Kemanusiaan LIPI di Provinsi Sumatra Selatan serta beberapa daerah di kawasan perbatasan Indonesia-Malaysia di Kalimantan Barat dan Utara. Hasil penelitian menunjukkan, pada 2014, perkebunan kelapa sawit telah menciptakan 5,3 juta kesempatan kerja di Indonesia. Di wilayah perbatasan, pengembangan kelapa sawit juga menciptakan kesempatan kerja bagi para TKI yang sebelumnya bekerja di Malaysia ataupun calon TKI yang akan bekerja di Malaysia. Namun, banyak perkebunan kelapa sawit yang belum dikelola secara berkelanjutan, sisi kelembagaan dan akses terhadap lahan. Kelembagaan yang lemah di perkebunan kelapa sawit menyebabkan sebagian koperasi (KUD) tidak mampu beroperasi. Di sisi lain, rendahnya akses terhadap lahan berdampak banyaknya konflik lahan yang terjadi perkebunan kelapa sawit. Keadaan tersebut berakibat rendahnya pendapatan tenaga kerja di perkebunan kelapa sawit. Perkebunan kelapa sawit berkelanjutan di Indonesia hanya dapat diciptakan melalui perbaikan kelembagaanpetani, akses terhadap lahan dan produktivitas lahan.Kata kunci: Kelapa sawit berkelanjutan, tenaga kerja perkebunan, Sumatra Selatan, kawasan perbatasan.